Training and sport performance in rhythmic gymnastics during competition period - Rutkauskaite, R.; Skarbalius, A. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
Aim of research was to analyze and to define 11-12 year (sport specialization stage) rhythmic gymnasts interaction between load, content and performance during competition period. Research objectives: 1) to define effective training program; 2) to define interaction between loads and results (to define gymnasts training loads and performance. Discussion: In co-coordination sport arts loads and intensity is all the time increasing. But the principle "more - helps more" is inoperative (Mester, Perl, 2000; 2001). Nowadays the problem is thus to create optimal and herewith effective training programs. That confirms our research: the effectiveness was determined by the rational using of loads (the best results had those programs in which loads were more optimal - 270 and 239 hours). Higher loads (309,42 hours) as well as the small loads (183 hours) were less effective. In comparison with preparatory period (Rutkauskaite, Skarbalius, 2003) reduced influence of choreography in most effective training programs (from 31% till 26%). Competition-like exercises and the establishment, perfection and mastering of the new technical elements were compensated by each other: that shows negative correlations (r= -0,48, r= -0,83, r= -0,73, r= -0,66). Physical training negative correlation with performing technical training in various programs, confirmed previous presumption that at the age of 11-12 years, the physical training loads increase in a natural way by introducing competition-like exercises. The research raises the problem of matching training loads, contents in the different competition microcycle during several months.